Application of modified linear regressive models for prognostication of progress in crop production - Дронь, В. С. (Scientific Progress & Innovations, 2012)
The use of modification of linear regressive models for research and prognostication of socio-economic figures, in particular in crop production, was offered. Modification is expedient at presence of additional information on connection between values. In the case of the known value of dependent variable at a specific value of the independent variable the point through which the regression line passes, is fixed. The example of application of the method for research of the productivity of winter wheat was offered. Comparison by the basic criteria of quality of the classic and modified regressive models was carried out.